TREATMENT OF CHRONIC HEART FAILURE: FOCUS ON METOPROLOL SUCCINATE - O. D. Ostroumova; G. N. Shchukina; V. M. Fomina (Столичная издательская компания, 2015)
Advantages of metoprolol succinate in patients with chronic heart failure (CHF) are covered. Results of MERIT-HF study are taken as the main evidences. Patterns of the metoprolol succinate use in the treatment of different categories of patients with CHF (women, the elderly , severe CHF forms, CHF with concomitant hypertension or diabetes) are considered.